Preparation method of two-dimensional single crystal rare earth compound nanosheet
Patent Information
- Application Number
- CN202510158856.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-13
AI Technical Summary
The prior art is difficult to efficiently and at low cost to prepare high-quality two-dimensional single-crystal rare earth compound nanosheets, especially while maintaining high rare earth element concentration and crystal quality, the growth rate is slow and costly.
Using chemical vapor deposition method, two-dimensional single-crystal rare earth compound nanosheets are generated by chemical reactions of rare earth element compounds and non-metallic catalysts on the substrate material. This method uses argon-hydrogen mixture as carrier gas and NaCl as catalyst to control the reaction temperature and heating rate to achieve efficient nanosheet growth.
It has achieved efficient and low-cost preparation of high-quality single-crystal rare earth compound nanosheets, with high crystal quality and rare earth element concentration, and is suitable for applications such as optoelectronic devices.
Smart Images

Figure CN119640395A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a method for preparing a two-dimensional single crystal rare earth compound nanosheet. Background Art
[0002] The 1.5μm band, as the optimal window for fiber-optic communications, plays a vital role in optical communication systems due to its low loss and high transmission efficiency. Rare earth elements, such as erbium (Er), have become a hot research topic in the field of optical communications due to their excellent luminescence properties in the 1.5μm communication band. Erbium's unique 4f electron structure endows it with a rich array of magnetic, electrical, and optical properties, enabling the fabrication of high-performance electronic devices such as field-effect transistors, magnetic memories, and sensors. Erbium also demonstrates broad application potential in biomedicine, energy storage, and catalysis. Material quality ultimately determines device performance, making high crystal quality and erbium concentration crucial in the development of these devices.
[0003] In the field of optoelectronic devices, traditional erbium-doped materials have low Er ion concentrations, which limits the optical gain per unit length. This makes devices based on erbium-doped materials large and difficult to integrate. This not only increases the cost of device preparation but also limits their application in highly integrated optoelectronic systems. Recent studies have found that Er compounds, due to their regular periodic arrangement, have Er ion concentrations that are 2-3 orders of magnitude higher than those of traditional erbium-doped materials, effectively alleviate concentration quenching, and provide higher gain. This high-concentration Er ion distribution offers significant advantages for Er compounds in optoelectronic devices such as optical amplifiers and lasers. Therefore, the synthesis and preparation of Er compounds and related devices that are easy to integrate on silicon have become a hot topic in silicon-based optoelectronics research.
[0004] Two-dimensional rare earth compound nanosheets are two-dimensional layered materials composed of rare earth elements and other elements, typically ranging in thickness from a few atomic layers to tens of nanometers. Because the layers are connected by van der Waals forces, they offer new avenues for silicon-based heterogeneous integration. Furthermore, due to their unique electronic structure and quantum confinement effects, these two-dimensional materials exhibit numerous novel physical phenomena, such as the quantum spin Hall effect, topological insulators, and superconductivity. The preparation of single-crystalline two-dimensional rare earth compound nanosheets provides an ideal platform for studying the structure-property relationships of these materials. By manipulating the composition, structure, and dimensionality of these materials, their physicochemical properties can be systematically investigated, providing theoretical guidance for the design of novel functional materials.
[0005] Traditional methods for synthesizing Er compounds include solvothermal, hydrothermal, and atomic layer deposition. These methods often face challenges such as complex growth processes, the need for metal catalysis, and difficulty in large-scale mass production. For example, solvothermal and hydrothermal methods typically require high temperature and high pressure, and the growth process is difficult to control, resulting in unstable product quality. Furthermore, the sol-gel method reported in prior art for growing Er2SiO5 uses a liquid-phase reaction to synthesize an Er2SiO5 solution. The solution is then spin-coated onto a substrate surface and evaporated to form a thin film. This method produces polycrystalline films with numerous defects and low luminescence efficiency. ALD (Atomic Layer Deposition) is a method for growing Er2O3. In a high-vacuum reaction chamber, gaseous precursors are precisely controlled and stepwise supplied to grow Er2O3 thin films on the substrate surface at atomic layer thickness. However, this method suffers from slow growth rates, making it unsuitable for large-scale production. Currently, methods for preparing two-dimensional rare earth compound nanosheets are not mature enough, making it difficult to obtain high-quality single-crystalline nanosheets. Therefore, new preparation methods are urgently needed to improve the crystalline quality and size of nanosheets.
[0006] Chemical vapor deposition (CVD) is a widely used technology for the preparation of nanomaterials. It deposits nanomaterials on the surface of a substrate through a gas-phase reaction. CVD technology has a simple principle and good controllability, making it suitable for the preparation of various nanomaterials, such as carbon nanotubes, graphene, transition metal sulfides (TMDs), etc. Although CVD has high growth control accuracy, it usually requires a metal catalyst, which increases the cost and complexity of the preparation. For example, the CVD method for growing ECS nanowires is to heat the precursor in a tube furnace to vaporize it, transport it through a carrier gas, and chemically react in the gas state or near the substrate surface to grow Er3Cl(SiO4)2 nanowires. However, this method is difficult to operate, requires particle catalysis, and is costly.
[0007] Therefore, how to efficiently and cost-effectively prepare rare earth compound nanomaterials with high crystal quality and high rare earth element concentration is a technical problem that needs to be solved urgently. Summary of the Invention
[0008] In view of the above problems existing in the prior art, the present invention provides a method for preparing two-dimensional single-crystal rare earth compound nanosheets, so as to efficiently and at low cost prepare rare earth nanomaterials with high crystal quality and high rare earth element concentration.
[0009] The present invention provides a method for preparing two-dimensional single crystal rare earth compound nanosheets, which adopts a chemical vapor deposition method to generate rare earth compound nanosheets on a substrate material, and comprises the following steps.
[0010] (1) Placing the substrate material into the reaction chamber; (2) The reactant gas enters the reaction chamber through the carrier gas, and the carrier gas flow rate and ratio are controlled; at the same time, the reaction chamber is heated, and the heating rate and temperature are controlled; the reactant includes a source material and a catalyst, the source material is a rare earth element compound, and the catalyst is a non-metallic catalyst; the mass ratio of the source material to the catalyst is 7:1~9:1.
[0011] (3) The solid matter generated by the reaction is deposited on the surface of the base material to form a thin film or coating, thereby obtaining single-crystal rare earth compound nanosheets.
[0012] The present invention provides a method for preparing two-dimensional single-crystalline rare earth compound nanosheets. The rare earth element compound is a compound with a high rare earth element ion content; preferably, a dysprosium compound, a holmium compound, an erbium compound, a thulium compound, an ytterbium compound, or a lutetium compound; more preferably, an erbium compound. In the present embodiment, ErCl₃ is selected as the source material. Those skilled in the art will appreciate that any erbium compound with a high Er ion content can be selected as the source material, not just ErCl₃.
[0013] According to the present invention, a method for preparing single-crystal rare earth compound nanosheets is provided, wherein the non-metallic catalyst is sodium chloride, potassium chloride, or an alkali metal chloride. In an embodiment of the present invention, NaCl is selected as a catalyst to promote the growth of Er compounds. NaCl has excellent thermal stability and catalytic properties, effectively promoting the growth of Er compounds at high temperatures while avoiding the use of metal catalysts.
[0014] According to a method for preparing a two-dimensional single crystal rare earth compound nanosheet provided by the present invention, the substrate material in step (1) is selected from silicon, silicon carbide, quartz, metal foil, germanium, gallium arsenide and / or gallium nitride; and / or Before step (1), the method further includes pre-treating the substrate material, wherein the pre-treatment comprises: ultrasonically cleaning the substrate material using an organic solvent (such as acetone, isopropyl alcohol) and deionized water to remove organic pollutants and impurities on the surface, drying the cleaned substrate material to remove residual moisture and solvent; and / or activating the substrate surface by plasma treatment, surface hydrophilic modification, physical vapor deposition or chemical pickling treatment to improve the bonding strength between the substrate material and the reactant.
[0015] During the specific implementation process, a suitable carrier gas and the flow rate of the carrier gas can be selected according to the reaction requirements of the rare earth compound and the non-metallic catalyst.
[0016] The present invention provides a method for preparing the above-mentioned two-dimensional single-crystal rare earth compound nanosheets, wherein the carrier gas in step (2) is an argon-hydrogen mixture, wherein the mixing ratio of argon and hydrogen is 95:5; or the carrier gas in step (2) is one of argon and nitrogen; and the carrier gas flow rate is 20 to 100 standard cubic centimeters per minute.
[0017] According to a method for preparing a two-dimensional single-crystal rare earth compound nanosheet provided by the present invention, the heating rate in step (2) is 18-21°C / min, the temperature is 750°C-1000°C; and / or the temperature is maintained for 20-60 minutes.
[0018] Under high temperature conditions, the rare earth compound, acting as a source material, and the non-metallic catalyst chemically react on the substrate surface, growing two-dimensional single-crystalline rare earth compound nanosheets. This reaction and growth process typically takes a certain amount of time, depending on the type of single-crystalline rare earth compound nanosheet to be grown and the growth conditions. In the present embodiment, the preparation time for the erbium compound nanomaterial was calculated from heating to the target temperature, maintaining the temperature at 900°C for a total of 60 minutes.
[0019] After obtaining the single-crystalline rare earth compound nanosheets in step (3) of the method for preparing a two-dimensional single-crystalline rare earth compound nanosheet provided by the present invention, the method further includes cooling the reaction chamber temperature, exhausting the remaining reactant gas and carrier gas, and transferring the grown nanomaterial from the substrate material using micro-nano transfer technology. Cooling to room temperature is generally sufficient. The cooling process is generally achieved by natural cooling or forced cooling to ensure that the nanomaterial does not undergo structural changes during the cooling process. Remaining reaction gas is exhausted from the reaction chamber by a vacuum pump to ensure that the interior of the reaction chamber is clean.
[0020] The high-quality single-crystalline compounds grown by this method can subsequently be transferred from a substrate to a target substrate using micro-nano transfer technology via dry transfer, enabling the realization of highly efficient coupled devices capable of silicon-based integration, such as silicon-based light sources and silicon-based optical amplifiers. Residual reactants and contaminants can be removed through thermal, chemical, or plasma treatments, thereby improving the purity and stability of the nanomaterials.
[0021] The present invention also provides a two-dimensional single crystal rare earth compound nanosheet, which is prepared by the preparation method described above.
[0022] Furthermore, the two-dimensional single-crystal rare earth compound nanosheet provided by the present invention is a single-crystal erbium compound nanosheet.
[0023] The method for preparing single-crystal erbium compound nanosheets provided by the present invention comprises: (1) placing a substrate material silicon into a reaction chamber; (2) a reactant gas enters the reaction chamber through a carrier gas (a mixture ratio of argon and hydrogen is 95:5), and the carrier gas flow rate is controlled to be 25 sccm standard cubic centimeters per minute; at the same time, the reaction chamber is heated, and the heating rate is controlled to be 20°C / minute to 900°C, and the temperature is maintained for 60 minutes; the reactants include a source material ErCl3 and a catalyst NaCl, and the mass ratio of ErCl3 to NaCl is 8:1; (3) a solid substance generated by the reaction is deposited on the surface of the substrate material to obtain a two-dimensional single-crystal rare earth compound nanosheet.
[0024] The present invention also provides a product containing the single crystal rare earth compound nanosheets as described above; the product includes optical communication devices, coupling devices, field effect transistors, photodetectors, solar cells, magnetic memories, biosensors, gas sensors, bioluminescent labeling instruments, quantum information devices, solid-state lighting components, lasers, amplifiers, catalysts, fuel cells or high-temperature superconducting materials.
[0025] The present invention also provides any of the following applications of the above preparation method or the above-mentioned single crystal rare earth compound nanosheets: (1) Amplify optical signals; (2) Preparation of fuel cells, lasers, catalysts, detectors, magnetic storage, sensors, transistors, and high-temperature superconducting materials; (3) Preparation of drug delivery systems to achieve targeted therapy; (4) Improve the photoelectric conversion efficiency of solar cells.
[0026] The present invention provides a method for preparing single-crystalline rare earth compound nanosheets. This method utilizes chemical vapor deposition (CVD) using a rare earth compound as a source material and a non-metallic catalyst to grow the single-crystalline rare earth compound nanosheets on a substrate. Because the reaction process does not require metal catalysis and the growth method is simple, it has the potential for large-scale mass production, enabling the efficient production of rare earth nanomaterials with high crystal quality and a high rare earth element concentration. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the present invention or the prior art, a brief introduction is given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0028] Figure 1 The present invention provides a process flow chart for the preparation of single-crystal rare earth compound nanosheets.
[0029] Figure 2 It is a schematic diagram of the reaction process provided by the present invention.
[0030] Figure 3 This is an optical microscope photograph of the single crystal erbium compound nanosheet provided by the present invention.
[0031] Figure 4 This is a scanning electron microscope photograph of the single crystal erbium compound nanosheet provided by the present invention.
[0032] Figure 5 It is a schematic diagram of the XRD results of the single crystal erbium compound nanosheet provided by the present invention.
[0033] Figure 6 The invention provides a high-resolution atomic arrangement of the single crystal erbium compound under a transmission electron microscope.
[0034] Figure 7 The present invention provides a luminescence spectrum of the single crystal erbium compound nanosheet in the 1.5 μm band at room temperature. DETAILED DESCRIPTION
[0035] To make the objectives, technical solutions, and advantages of the present invention more clear, the technical solutions of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.
[0036] The following combination Figure 1 The invention describes a method for preparing single crystal rare earth compound nanosheets.
[0037] Figure 1 The process flow chart of the preparation method of the single crystal rare earth compound nanosheet provided by the present invention is as follows: Figure 1 As shown, the method includes the following steps: Step S1: placing the substrate material into the reaction chamber.
[0038] In the specific implementation process, the substrate can be selected according to the properties of the nanomaterial to be prepared and the application requirements. The substrate material is selected from silicon, silicon carbide, quartz, metal foil, germanium, gallium arsenide and / or gallium nitride materials.
[0039] The reaction chamber is used for chemical vapor deposition. This step also includes a pretreatment of the substrate material. This pretreatment includes ultrasonic cleaning of the substrate using an organic solvent (e.g., acetone, isopropyl alcohol) and deionized water to remove organic contaminants and impurities on the surface, followed by drying the cleaned substrate to remove residual moisture and solvent. Furthermore, the substrate surface may be activated through plasma treatment, surface hydrophilic modification, physical vapor deposition, or chemical pickling to enhance the bonding between the substrate and the reactants.
[0040] In step S2, the reactant gas enters the reaction chamber through the carrier gas, and the carrier gas flow rate and ratio are controlled; at the same time, the reaction chamber is heated, and the heating rate and temperature are controlled; the reactants include a source material and a catalyst, the source material is a rare earth element compound, and the catalyst is a non-metallic catalyst; the mass ratio of the source material to the catalyst is 7:1 to 9:1.
[0041] The rare earth element compound is a compound with a high rare earth element ion content; preferably, it is a dysprosium compound, a holmium compound, an erbium compound, a thulium compound, a ytterbium compound, or a lutetium compound; preferably, it is an erbium compound.
[0042] Non-metallic catalysts include sodium chloride NaCl, potassium chloride and alkali metal chlorides.
[0043] Non-metallic catalysts are used to promote the growth of rare earth compounds. Among them, NaCl has good thermal stability and catalytic properties, effectively promoting the growth of rare earth compounds at high temperatures while avoiding the use of metal catalysts, effectively reducing production costs.
[0044] During the specific implementation process, a suitable carrier gas and the flow rate of the carrier gas can be selected according to the reaction requirements of the rare earth compound and the non-metallic catalyst.
[0045] The gas injection system injects carrier gas into the reaction chamber, precisely controlling its flow rate and ratio. Flow rate control is achieved using a mass flow controller (MFC) to ensure that the gas ratio and concentration meet the requirements for rare earth compound growth. The flow rate affects the pressure within the tube and the nucleation conditions on the substrate surface, and therefore needs to be adjusted based on the specific situation.
[0046] Exemplarily, the carrier gas is an argon-hydrogen mixture, wherein the mixing ratio of argon and hydrogen is 95:5, or the carrier gas is one of argon and nitrogen; the carrier gas flow rate is 20 to 100 standard cubic centimeters per minute.
[0047] During the specific implementation process, the reaction chamber can be heated by resistance heating or induction heating until the temperature inside the reaction chamber reaches a preset temperature.
[0048] The temperature range of the reaction chamber is determined by the properties of the rare earth compounds and non-metallic catalysts involved in the reaction. Heating rate and temperature control are crucial to the quality of rare earth nanomaterial growth. Too low a growth temperature can't guarantee the supply of source materials, affecting production efficiency. Too high a growth temperature can lead to excessively high rare earth element concentrations, preventing sufficient oxidation by the atmosphere within the tube, affecting the growth process and single crystal quality.
[0049] High-quality single crystal growth of rare earth compounds can be ensured by precisely controlling the temperature, gas pressure and carrier gas flow rate in the reaction chamber.
[0050] Exemplarily, the heating rate is 18-21 degrees Celsius per minute, the preset temperature is 750° C.-1000° C.; and / or the temperature is maintained for 20-60 minutes.
[0051] Step S3: The solid matter generated by the reaction is deposited on the surface of the base material to form a thin film or coating to obtain single crystal rare earth compound nanosheets.
[0052] In some embodiments, the single crystalline rare earth compound nanosheets are single crystalline erbium compound nanosheets.
[0053] Single-crystal rare earth compound nanosheets are two-dimensional layered materials composed of rare earth elements and other elements, typically ranging in thickness from a few atomic layers to tens of nanometers. Because the layers are connected by van der Waals forces, these materials offer new avenues for silicon-based heterogeneous integration. Furthermore, these two-dimensional materials, due to their unique electronic structure and quantum confinement, exhibit numerous novel physical phenomena, such as the quantum spin Hall effect, topological insulators, and superconductivity.
[0054] The preparation of single-crystalline rare earth compound nanosheets provides an ideal platform for studying the structure-property relationship of materials. By manipulating the composition, structure, and dimensions of the materials, their physical and chemical properties can be systematically studied, providing theoretical guidance for the design of new functional materials.
[0055] After obtaining the single crystal rare earth compound nanosheets, the process also includes cooling the reaction chamber temperature, discharging the remaining reactant gas and carrier gas, and transferring the grown nanomaterials from the substrate material through micro-nano transfer technology.
[0056] The cooling process is typically achieved through natural cooling or forced cooling to ensure that the single-crystal rare earth compound nanosheets do not undergo structural changes during the cooling process. Remaining reaction gases are exhausted from the reaction chamber using a vacuum pump to ensure a clean interior.
[0057] By using micro-nano transfer technology, such as dry transfer, the grown single-crystalline rare earth compound nanosheets are transferred from the substrate to the target substrate, and efficient coupling devices that can be integrated on silicon can be realized, such as silicon-based light sources and silicon-based optical amplifiers.
[0058] A specific embodiment of the present invention further provides a single crystal rare earth compound nanosheet prepared as described above.
[0059] In some embodiments, the single-crystalline rare earth compound nanosheet is a single-crystalline erbium compound nanosheet.
[0060] Example 1 Silicon wafer was selected as the substrate material.
[0061] Ultrasonic cleaning of the substrate using an organic solvent (e.g., acetone, isopropyl alcohol) and deionized water removes organic contaminants and impurities from the surface. The cleaned substrate is then dried at high temperature to remove any residual water and solvent. The substrate surface is then activated using plasma treatment or chemical treatment (e.g., acid cleaning) to enhance its binding strength with the nanomaterial.
[0062] Erbium trichloride (ErCl3) was selected as the source material to provide erbium ions. Sodium chloride (NaCl) was selected as the catalyst. NaCl has good thermal stability and catalytic properties, and can effectively promote the growth of erbium compounds at high temperatures while avoiding the use of metal catalysts.
[0063] like Figure 2 As shown, a reactant gas consisting of an erbium compound and sodium chloride in a ratio of 8:1 is introduced into a reaction chamber via a carrier gas composed of a 95:5 mixture of argon and hydrogen. The carrier gas flow rate is controlled at a standard cubic centimeter per minute. Simultaneously, the reaction chamber is heated at a rate of 20°C per minute to a temperature of 900°C. After maintaining this temperature for 60 minutes, the solid material generated by the reaction is deposited on the surface of the substrate, forming a thin film or coating, resulting in single-crystalline erbium compound nanosheets.
[0064] Figure 3 shows an optical microscope photograph of the single crystal erbium compound nanosheet provided by the present invention, Figure 4 Figure 2 shows a scanning electron microscope photo of a single crystal erbium compound nanosheet provided by the present invention. Figure 3 、 Figure 4 As shown, the single-crystalline erbium compound nanosheets provided by the present invention have a regular polygonal structure consistent with the lattice structure, and the edges are very smooth, proving that their growth follows the lattice arrangement rules and has the characteristics of small size, thin thickness, high specific surface area, etc. Therefore, the single-crystalline erbium compound nanosheets provided by the present invention have high crystal quality.
[0065] Figure 5 A schematic diagram of the XRD (X-ray diffraction) results of the single-crystal erbium compound nanosheet provided by the present invention is shown. Figure 5In the figure, the red curve represents the grown sample (single crystal erbium compound nanosheet), while the black curve represents the standard diffraction data (PDF-ErOCI) of erbium oxyhalide (ErOCI). By comparing the two curves, it can be observed that the diffraction peak position of the grown sample is basically consistent with the standard peak position of PDF-ErOCI, and the main diffraction peaks appear at angles of approximately 10° and 30°, respectively. This result indicates that the crystal structure of the synthesized single crystal erbium compound nanosheet matches the known ErOCI crystal structure, thereby confirming that the sample is erbium oxyhalide (for example, ErOCI), because the theoretical concentration of Er particles in erbium oxyhalide is 1.7×1022cm-3, which is 2-3 orders of magnitude higher than the concentration of erbium-doped materials. Therefore, the single crystal erbium compound nanosheet provided by the present invention has a higher erbium ion concentration, which can effectively alleviate the concentration quenching phenomenon and can provide higher gain for optoelectronic devices such as optical amplifiers and lasers. And Figure 5 In the diffraction peak, there is a sharp peak without impurity peaks, which proves that the single crystal erbium compound nanosheet provided by the present invention has no impurity phase and has high growth purity.
[0066] Figure 6 The figure shows the high-resolution atomic arrangement of the single crystal erbium compound provided by the present invention under a transmission electron microscope. Figure 6 As shown, the single-crystal erbium compound nanosheet has a regular atomic arrangement, which also proves that the single-crystal erbium compound nanosheet provided by the present invention has a high crystal quality.
[0067] Figure 7 The luminescence spectrum of the single crystal erbium compound nanosheet provided by the present invention at 1.5 μm band at room temperature is shown. Figure 7 As shown, the single-crystal erbium compound nanosheets provided by the present invention exhibit distinct luminescence peaks in the 1.5-micron wavelength band, particularly at 1537 nm and 1543 nm, demonstrating strong luminescence. The peaks have narrow half-widths of 2.5 nm and 3.8 nm, respectively, which helps improve spectral resolution and signal quality. Furthermore, the single-crystal erbium compound nanosheets maintain stable luminescence properties even at room temperature, eliminating the need for specialized cryogenic environments and possessing broad potential for application.
[0068] A specific embodiment of the present invention further provides a product containing the single crystal rare earth compound nanosheets described above.
[0069] The products include optical communication devices, coupling devices, field-effect transistors, photodetectors, solar cells, magnetic storage, biosensors, gas sensors, bioluminescent labeling instruments, quantum information devices, solid-state lighting components, lasers, amplifiers, catalysts, fuel cells or high-temperature superconducting materials, etc.
[0070] A specific embodiment of the present invention further provides any of the following applications using the above-described method for preparing single-crystalline rare earth compound nanosheets or the above-described single-crystalline rare earth compound nanosheets: (1) Amplify the optical signal.
[0071] (2) Preparation of fuel cells, lasers, catalysts, detectors, magnetic storage devices, sensors, transistors, and high-temperature superconducting materials.
[0072] (3) Prepare drug delivery systems to achieve targeted therapy.
[0073] (4) Improve the photoelectric conversion efficiency of solar cells.
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.
Claims
1. A method for preparing a two-dimensional single crystal rare earth compound nanosheet, characterized in that: A chemical vapor deposition method is used to generate rare earth compound nanosheets on a substrate material, comprising the steps of: (1) Placing the substrate material into the reaction chamber; (2) The reactant gas enters the reaction chamber through the carrier gas, and the carrier gas flow rate and ratio are controlled; the reaction chamber is heated at the same time, and the heating rate and temperature are controlled; the reactant includes a source material and a catalyst, the source material is a rare earth element compound, and the catalyst is a non-metallic catalyst; the mass ratio of the source material to the catalyst is 7:1 to 9:1; (3) The solid substance generated by the reaction is deposited on the surface of the base material to form a thin film or coating, thereby obtaining a two-dimensional single crystal rare earth compound nanosheet.
2. The preparation method according to claim 1, characterized in that: The rare earth element compound is a dysprosium compound, a holmium compound, an erbium compound, a thulium compound, a ytterbium compound, or a lutetium compound.
3. The preparation method according to claim 2, characterized in that: The non-metal catalyst is sodium chloride, potassium chloride, or alkali metal chloride.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The substrate material in step (1) is selected from silicon, silicon carbide, quartz, metal foil, germanium, gallium arsenide and / or gallium nitride; and / or Prior to step (1), the step of pre-treating the substrate material is also included, wherein the pre-treatment comprises: ultrasonically cleaning the substrate material using an organic solvent and deionized water to remove organic pollutants and impurities on the surface, drying the cleaned substrate material to remove residual moisture and solvent; and / or activating the substrate surface by plasma treatment, surface hydrophilic modification, physical vapor deposition or chemical pickling treatment to improve the bonding strength between the substrate material and the reactant.
5. The preparation method according to claim 4, characterized in that: The carrier gas in step (2) is an argon-hydrogen mixture, wherein the mixing ratio of argon to hydrogen is 95:5; or In step (2), the carrier gas is one of argon and nitrogen; and the carrier gas flow rate is 20 to 100 standard cubic centimeters per minute.
6. The preparation method according to claim 5, characterized in that: In step (2), the heating rate is 18-21°C / min, the temperature is 750°C-1000°C; and / or the temperature is maintained for 20-60 minutes.
7. A two-dimensional single crystal rare earth compound nanosheet, prepared by the preparation method according to any one of claims 1 to 6. The two-dimensional single-crystalline rare earth compound nanosheet according to claim 7 , which is a single-crystalline erbium compound nanosheet.
9. A product containing the two-dimensional single-crystalline rare earth compound nanosheet according to claim 7 or 8; the product includes optical communication devices, coupling devices, field effect transistors, photodetectors, solar cells, magnetic storage devices, biosensors, gas sensors, bioluminescent labeling instruments, quantum information devices, solid-state lighting components, lasers, amplifiers, catalysts, fuel cells or high-temperature superconducting materials.
10. Use of the preparation method according to any one of claims 1 to 6 or the two-dimensional single crystal rare earth compound nanosheet according to any one of claims 7 to 8 in any of the following: (1) Amplify the optical signal; (2) Preparation of fuel cells, lasers, catalysts, detectors, magnetic storage, sensors, transistors, and high-temperature superconducting materials; (3) Preparation of drug delivery systems to achieve targeted therapy; (4) Improve the photoelectric conversion efficiency of solar cells.
Citation Information
Patent Citations
Method for preparing large-size single crystal two-dimensional material based on chemical vapor deposition
CN113737277A
Ultrathin two-dimensional CoO single-crystal nanosheet as well as preparation method and application thereof
CN116732605A
Rare earth element doped WS2 nanosheet as well as preparation method and application thereof
CN118166418A
Preparation method and application of two-dimensional ErOCl thin film material
CN118932483A
Method of making supersaturated rare earth doped semiconductor layers by chemical vapor deposition
US5322813A